The Effect of Advanced Platelet-Rich Fibrin Plus (A-PRF+) on Graft Stability in Dental Implants and Alveolar Ridge Augmentation Procedures: A New Low-Speed Standardized Centrifugation Protocol - Benjamin Walch; Andreas Kolk; Dominik Scheibl; Maria Guarda; Sarah Christine Maier; Lena Denk (MDPI AG, 2024)
Background: Platelet-rich fibrin (PRF) is a concentrate derived from autologous blood, containing platelets, fibrin, and growth factors (GF) obtained through centrifugation. PRF can be mixed with bone replacement material to form sticky bone, which is then introduced into the desired area for stabilizing and graft-covering. Depending on the centrifugation protocol, the effectiveness of the end products can vary. This controlled clinical study examines the impact of our established PRF protocol in alveolar augmentation and dental implant placement on vertical bone loss. Materials and Methods: A total of 362 implants were performed in 170 patients at the Department of Oral and Maxillofacial Surgery at the University Hospital Innsbruck between 2018 and 2021. After accounting for lost implants, we retrospectively evaluated a radiological vertical bone loss exceeding 1 mm in the first year as the primary endpoint. Results: The use of PRF was significantly associated with vertical bone loss > 1 mm (OR = 0.32, 95% CI (0.13-0.81), p = 0.016). There were no significant associations between PRF and the number of implants lost, the type of augmentation, or bone loss. Discussion: A-PRF+ sticky bone grafts, when combined with bone graft materials, show reduced resorption rates, indicating their potential to enhance graft stability in oral implantology. Our data indicate that the Medifuge MF 100 (Silfradent srl, Forlì, Italy) is effective in producing A-PRF+.